2017 IEEE 29th International Conference on Tools With Artificial Intelligence (ICTAI) 2017
DOI: 10.1109/ictai.2017.00020
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Mammal Genera on Camera-Trap Images Using Multi-layer Robust Principal Component Analysis and Mixture Neural Networks

Abstract: The segmentation and classification of animals from camera-trap images is due to the conditions under which the images are taken, a difficult task. This work presents a method for classifying and segmenting mammal genera from camera-trap images. Our method uses Multi-Layer Robust Principal Component Analysis (RPCA) for segmenting, Convolutional Neural Networks (CNNs) for extracting features, Least Absolute Shrinkage and Selection Operator (LASSO) for selecting features, and Artificial Neural Networks (ANNs) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Even so, the accuracies that were achieved, for example, 82% by Yu et al (2013), were not comparable to human accuracies of 96.6% (Swanson et al, 2016). More recent studies in automatically identifying animal species using CNNs have reported accuracies around 90% with some manual preprocessing (Gomez Villa et al, 2017) or more complex pipelines involving automatic preprocessing (Giraldo-Zuluaga, Salazar, Gomez, & Diaz-Pulido, 2017). The most recent advances by Norouzzadeh et al (2018) have reported accuracies of 93.8% and have matched human accuracy on over 99% of all images.…”
Section: Automatic Animal Identificationmentioning
confidence: 94%
See 1 more Smart Citation
“…Even so, the accuracies that were achieved, for example, 82% by Yu et al (2013), were not comparable to human accuracies of 96.6% (Swanson et al, 2016). More recent studies in automatically identifying animal species using CNNs have reported accuracies around 90% with some manual preprocessing (Gomez Villa et al, 2017) or more complex pipelines involving automatic preprocessing (Giraldo-Zuluaga, Salazar, Gomez, & Diaz-Pulido, 2017). The most recent advances by Norouzzadeh et al (2018) have reported accuracies of 93.8% and have matched human accuracy on over 99% of all images.…”
Section: Automatic Animal Identificationmentioning
confidence: 94%
“…(), were not comparable to human accuracies of 96.6% (Swanson et al., ). More recent studies in automatically identifying animal species using CNNs have reported accuracies around 90% with some manual preprocessing (Gomez Villa et al., ) or more complex pipelines involving automatic preprocessing (Giraldo‐Zuluaga, Salazar, Gomez, & Diaz‐Pulido, ). The most recent advances by Norouzzadeh et al.…”
Section: Introductionmentioning
confidence: 99%
“…These standards are a powerful tool to environmentalists as camera traps can document all wildlife aspects. Camera trapping is being carried out quickly in the field of wildlife monitoring with digital technological improvements, which produce more contemporary camera traps with system part automation, but reduce costs for procurement [26,38]. Although the human visual system can quickly and easily process images, manually manipulating such a large amount of images is still very costly.…”
Section: Animal Detection Methods In Field Of Image Processingmentioning
confidence: 99%
“…Animal segmentation using Multi-Layer Robust Principal Component Analysis involving color and texture features was proposed in [16]. This approach was further combined with deep learning methods in [15]. Both works are evaluated on camera trap data from a Colombian forest.…”
Section: Automated Wildlife Surveillancementioning
confidence: 99%